Gate-tunable charge carrier electrocaloric effect in trilayer graphene - Natalia Cortés (Nature Portfolio, 2021)
Abstract The electrocaloric (EC) effect is the change in temperature and entropy of a material driven by the application of an electric field. Our tight-binding calculations linked to Fermi statistics, show that the EC effect can be produced in trilayer graphene (TLG) structures connected to a heat source, triggered by changes in the electronic density of states (DOS) at the Fermi level when external gate fields are applied on the outer graphene layers. We demonstrate that entropy changes are sensitive to the stacking arrangement in TLG systems. The AAA-stacked TLG presents an inverse EC response (cooling) regardless of the temperature value and gate field potential strength, whereas the EC effect in ABC-stacked TLG remains direct (heating) above room temperature. We reveal otherwise the TLG with Bernal-ABA stacking generates both the direct and inverse EC response within the same sample, associated with gate-dependent electronic transitions of thermally excited charge carriers from the valence band to the conduction band in the band structure. The novel charge carrier electrocaloric effect we propose in quantum layered systems may bring a wide variety of prototype van der Waals materials that could be used as versatile platforms to controlling the thermal response in nanodevices.